1996
DOI: 10.1002/(sici)1096-9071(199602)48:2<141::aid-jmv4>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of arthropod-borne viruses and other infectious disease pathogens as the causes of febrile illnesses in the Khartoum Province of Sudan

Abstract: The relative importance of arthropod-borne and other disease pathogens as the cause of an outbreak of febrile illnesses was assessed during August 1988, following severe flooding in Khartoum, Sudan. A total of 200 patients with acute febrile illness and 100 afebrile controls were enrolled in the study during October and November 1988; at the Omdurman Military Hospital, Khartoum, Sudan. Sera were tested for IgM and IgG antibodies to six arthropod-borne viruses by an enzyme-linked immunoabsorbent assay, and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 6 publications
1
53
0
Order By: Relevance
“…12 In Senegal, 185 strains of Chikungunya virus were isolated from 13 mosquito species. Although the infection rates are high in some mosquito species, epidemics seem to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…12 In Senegal, 185 strains of Chikungunya virus were isolated from 13 mosquito species. Although the infection rates are high in some mosquito species, epidemics seem to be rare.…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of IgM antibodies against dengue virus (types 1-4), West Nile virus, yellow fever virus, and Sindbis virus, an IgM capture ELISA was used as previously described. 6,16,17 IgM antibodies against Rift Valley fever virus, Chikungunya virus, Crimean Congo hemorrhagic fever virus, and R. typhi were measured by an indirect immunofluorescence assay as described. 18,19 Detection of IgG antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In sub-Saharan African countries such as in Zaire, 3 Uganda, 4 Sudan, 5,6 and Kenya, 7 several outbreaks of febrile illness have been associated with arbovirus infections. Both sporadic and major outbreaks of West Nile fever have also been reported in Europe, with the largest in Romania, which had 393 serologically confirmed cases.…”
mentioning
confidence: 99%
“…106 One time series study using health and demographic data found a moderate increase in acute respiratory infections (RR: 1.25; 95% CI, 1.06-1.47) within six months after a flood. 102 Two studies of patients presenting at treatment facilities with acute fever identified malaria in 22% of the patients, 107 dengue fever in 29.4%, and scrub typhus in 1.1% 105 within two to three months and one month post-flood, respectively, and no change was seen in the proportion of people diagnosed with dengue fever who lived in flooded areas four weeks after a flood. 106 A surveillance system study of multiple diseases gave seven alerts for suspected measles, one alert for acute hemorrhagic fever syndrome, two alerts for suspected meningitis, and two alerts for suspected poliomyelitis, but no alerts for acute respiratory infection or unexplained fever in the seven weeks after a flood.…”
Section: Treatment Facility Presentations (%)mentioning
confidence: 99%